2016
DOI: 10.1111/jam.13174
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic and antimicrobial activity of volatile and semi-volatile organic compounds from the endophyteHypoxylon anthochroumstrain Blaci isolated fromBursera lancifolia(Burseraceae)

Abstract: This work firstly reports the phytotoxic activity of volatile and semi-volatile compounds produced by the endophyte H. anthochroum strain Blaci on seed germination, root elongation, and seedling respiration of four different plants; consequently, these compounds could be useful in biocontrol of weeds and plant pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 56 publications
2
29
0
3
Order By: Relevance
“…However, these experiments revealed that some of these volatiles at high concentrations (100 μM or more) negatively influenced A . thaliana growth, consistent with previous results (Splivallo et al, ; Ulloa‐Benítez et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, these experiments revealed that some of these volatiles at high concentrations (100 μM or more) negatively influenced A . thaliana growth, consistent with previous results (Splivallo et al, ; Ulloa‐Benítez et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Also, MB and PA, found in the volatiles of truffles, inhibited the germination and development of Arabidopsis at high concentrations (above 100 μM; Splivallo, Novero, Bertea, Bossi, & Bonfante, ). Also, PA produced by an endophytic fungus inhibited germination and growth of Amaranthus hypochondriacus , Panicum miliaceum , Trifolium pretense , and Medicago sativa at concentrations higher or equal to 12.5 μg ml −1 (102.31 μM; Ulloa‐Benítez et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Pure phenylethyl alcohol and eucalyptol were also evaluated in the same vegetal processes, displaying IC 50 values between 21.4 µg/mL and > 500.0 µg/mL, and 11.6 µg/ mL and > 500.0 µg/mL, respectively. The IC 50 values of the positive control Rival were found between 14.8 µg/mL and > 500.0 µg/mL [87].…”
Section: Hypoxylon Anthochroummentioning
confidence: 93%
“…In this context, E. gomezpompae was isolated from surface sterilized leaves of the medicinal plant C. acuminata [73]. A chemical investigation of the mycelium of E. gomezpompae resulted in the isolation of eight naphthoquinone-spiroketals, namely, preussomerins EG 1 -EG 4 (85)(86)(87)(88), palmarumycins EG 1 (89), CP 2 (90), CP 17 (91), and CP 19 (92) as well as 50 [74,75] (▶ Fig. 14).…”
Section: Endophytes From Plants Collected In El Eden Ecological Resermentioning
confidence: 99%
See 1 more Smart Citation